2011
DOI: 10.1074/jbc.m110.118018
|View full text |Cite
|
Sign up to set email alerts
|

Arrestin-2 Differentially Regulates PAR4 and ADP Receptor Signaling in Platelets

Abstract: Arrestins can facilitate desensitization or signaling by G protein-coupled receptors (GPCR) in many cells, but their roles in platelets remain uncharacterized. Because of recent reports that arrestins can serve as scaffolds to recruit phosphatidylinositol-3 kinases (PI3K)s to GPCRs, we sought to determine whether arrestins regulate PI3K-dependent Akt signaling in platelets, with consequences for thrombosis. Co-immunoprecipitation experiments demonstrate that arrestin-2 associates with p85 PI3K␣/␤ subunits in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
58
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 34 publications
5
58
1
Order By: Relevance
“…The sequential activation of PAR1 and PAR4 by thrombin may allow the receptors to rearrange in the platelet membrane and alter the signaling response. A recent study by Li et al (49) described how PAR4 cooperates with the ADP receptor, P2Y12. In these studies platelets from arrestin-2-deficient mice had a reduction in Akt phosphorylation and fibrinogen binding in response to PAR4 activation.…”
Section: Discussionmentioning
confidence: 99%
“…The sequential activation of PAR1 and PAR4 by thrombin may allow the receptors to rearrange in the platelet membrane and alter the signaling response. A recent study by Li et al (49) described how PAR4 cooperates with the ADP receptor, P2Y12. In these studies platelets from arrestin-2-deficient mice had a reduction in Akt phosphorylation and fibrinogen binding in response to PAR4 activation.…”
Section: Discussionmentioning
confidence: 99%
“…27 To determine whether L5 activates platelets through the PKCa signaling pathway, we examined the activity and activation of PKCa in human platelets exposed to L5 from STEMI patients. In the lysate of L5-treated platelets, total PKC activity was increased (data not shown).…”
Section: L5-mediated Activation Of Human Platelets Requires the Pkcamentioning
confidence: 99%
“…PARs are no exception as evidence exists for both constitutive and agonist-induced dimers. 8,23,[75][76][77][78] The major point of contention regarding the organization of GPCRs is defining a reliable readout for oligomerization of receptors in native tissues. PARs have a distinct advantage over other receptor families because they cooperate in specific ways that are consistent with dimerization or oligomerization.…”
mentioning
confidence: 99%
“…23,78,79 In platelets, PAR4 also forms agonist dependent heterodimers with the ADP receptor, P2Y12. 76,77 Li et al showed that simultaneous stimulation of PAR4 and P2Y12 resulted in arrestin-2 recruitment to PAR4. 77 Following recruitment, arrestin-2 served as a scaffold to support Akt signaling.…”
mentioning
confidence: 99%
See 1 more Smart Citation